Transcriptome-Wide Dynamics of m6A Methylation in Tumor Livers Induced by ALV-J Infection in Chickens - Zhao, Qiqi; Yao, Ziqi; Chen, Liyi; He, Yaai; Xie, Zi; Zhang, Huanmin; Lin, Wencheng; Chen, Feng; Xie, Qingmei; Zhang, Xinheng (Frontiers in Immunology, 2022)
Avian Leukosis Virus Subgroup J (ALV-J) is a tumorigenic virus with high morbidity and rapid transmission. N6-methyladenosine (m6A) is a common epigenetic modification that may be closely related to the pathogenicity of ALV-J. Currently, there are no reports on whether m6A modification is related to ALV-J induced tumor formation. In this study, we used methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) to examine the differences in m6A methylation and gene expression in normal livers and ALV-J-induced tumor livers systematically, with functional enrichment and co-expression analysis. The results identified 6,541 m6A methylated peaks, mainly enriched in CDS, and more than 83% of the transcripts contained 1-2 m6A peaks. For RNA-seq, 1,896 and 1,757 differentially expressed mRNAs and lncRNAs were identified, respectively. Gene enrichment analysis indicated that they may be involved in biological processes and pathways such as immunology-related and apoptosis. Moreover, we identified 17 lncRNAs, commonly existing in differently expressed methylome and transcriptome. Through co-expression analysis, 126 differentially expressed lncRNAs, and 18 potentially m6A-related methyltransferases were finally identified and connected, suggesting that m6A modifications might affect gene expression of lncRNAs and play a role in ALV-J induced tumor formation. This study provides the first comprehensive description of the m6A expression profile in tumor livers induced by ALV-J infection in chickens, which provides a basis for studying the role of m6A modification in ALV-J induced tumorigenesis. This study provides clues for studying the epigenetic etiology and pathogenesis of ALV-J.